2022
DOI: 10.1111/1750-3841.16130
|View full text |Cite
|
Sign up to set email alerts
|

Purple sweet potato anthocyanin extract regulates redox state related to gut microbiota homeostasis in obese mice

Abstract: This study explored the advantageous effects of purple sweet potato anthocyanin extract (PSPAE) on redox state in obese mice. The normal chow diet (NCD) group, high‐fat/cholesterol diet (HCD) group, and three groups based on HCD and added with low, middle, and high dose of PSPAE (PAL, PAM, and PAH) were raised for 12 weeks. High dose of PSPAE treatment decreased the elevations of the body weight by 24.7%, serum total cholesterol by 48.3%, serum triglyceride by 42.4%, and elevated serum activities of glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…This systematic review and meta-analysis demonstrated that dietary anthocyanin supplementation profoundly improves rodent models' gut health biomarkers (Fir/Bac and SCFAs). This finding was supported by studies carried out after cut off time limit of this studies [77][78][79][80][81] . According to certain research articles, the Fir/Bac ratio is a defining characteristic of obesity.…”
Section: Discussionsupporting
confidence: 83%
“…This systematic review and meta-analysis demonstrated that dietary anthocyanin supplementation profoundly improves rodent models' gut health biomarkers (Fir/Bac and SCFAs). This finding was supported by studies carried out after cut off time limit of this studies [77][78][79][80][81] . According to certain research articles, the Fir/Bac ratio is a defining characteristic of obesity.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, measuring GSH-PX activity can indirectly reflect the degree of damage to organ function in diabetic mice. In our study, after PSPA intervention, the GSH-PX concentration in mouse serum significantly increased, which helped maintain homeostasis in the physiological environment to a certain extent [ 20 ]. reported a similar effect, showing that a high dose of PSPA extract (917 mg/kg body weight) increased the antioxidant capacity (catalase, GSH-PX, and superoxide dismutase activities) and reduced malondialdehyde concentration in the serum and liver of obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…After one week of acclimatization, the mice were randomly divided into five groups: control (C), model (M), low- (LP, 227.5 mg/kg), medium- (MP, 455 mg/kg), and high-dose (HP, 910 mg/kg) PSPA (13 mice in each group), the dosages of PSPA were referred to Ref. [ 20 ]. Group C was fed a maintained diet, the M, LP, MP, and HP groups were fed a high-fat diet (HFD), the energy supply ratio of protein, fat, and carbohydrate are 20.6 %, 12 %, 67.4 %, and 19.07 %, 60.34 %, 20.59 %, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Clostridium spp. is positively correlated with chronic infammation, serum TG, TC, and TNF-α levels [34], and TNF-α can activate various signaling cascades and induce insulin resistance. Akkermansia is negatively correlated with obesity and diabetes.…”
Section: Discussionmentioning
confidence: 99%